The predictive validity and temporal characteristics of the HCR-20v3 for inpatient violence in forensic inpatient settings: an international study - Picchioni, Marco; Ruiz, Rebecca; de Girolamo, Giovanni; Iozzino, Laura; Zamparini, Manuel; Wancata, Johannes; Unger, Annemarie; Heitzman, Janusz; Markewitz, Inga; Dreßing, Harald; Large, Matthew M. (Psychiatry research, 2024)
Aggression and violence are common day to day problems in psychiatric settings. However, the optimal means of assessing that risk remains unclear. In the context of that uncertainty many tools have evolved, among which the HCR-20 is one of the most globally accepted, though many questions remain about its performance, how and when it should be deployed and how it can be most effectively used. In this 12 month follow up study of 210 forensic psychiatric inpatients with a diagnosis of a schizophrenia spectrum disorder we explored these issues. We found that the performance of the HCR-20v3, especially its Total score, performed well up to 6 months after it was rated but its performance deteriorated after that. Repeating the HCR-20v3 at 6 months stabilised the risk assessment and led to improved performance in the second months over and above the first rating. The HCR-20v3 was good at identifying those subjects at low risk of violence over 6 months of follow up in a forensic inpatient setting. The real-world implications of this study are that the HCR-20v3 is an effective means of identifying patient at low risk of violence, but it should be reassessed every 6 months.
Gesehen am 31.03.2025